Pertumbuhan dan Produksi Okra (Abelmoschus esculentus L.) pada Level Pemupukan dan Jarak Tanam yang Berbeda - Jessica Raditya; Endang Dwi Purbajanti; Widyati Slamet (Journal of Agro Complex, 2017)
This research aimed to study the growth and yield of Okra at different nitrogen fertilizer levels and plant spacing. The experiment was assigned in a completely randomized factorial design with plant spacing (50x50 and 50x75 cm) as the first factor and nitrogen fertilizer level (0, 50, 100, 150 kg N/ha) as the second factor. Each treatments was repeated three times. Parameters measured were stem diameter, number of leaves, number of fruits per plot, and weight of fruits per plot. Data were subjected to ANOVA and followed by Duncan’s Multiple Range Test (DMRT). The result showed that adding 50 kg N/ha increased stem diameter and number of leaves. The treatment of 50x50 cm spacing and 150 kg N/ha dose had the highest number of fruits per plot and weight of fruits per plot, and significantly different with 0 kg N/ha dose treatment in all parameters.